LANGUAGE OF COLORS: रंगों की भाषा - Jain, Sandhya (International Journal of Research -GRANTHAALAYAH, 2014)
Colors have their own language. Color is our life. These colors spread their color in different walks of life. Food, food, living, worship, religious activities are all associated with different colors. Every person in this theater of the world is painted in some or the other color. The feeling of colors comes from seeing and touching. Our life without colors is the same as that of a body without life. In nature beauty, where these colors apply four moons, while human life also makes it succulent, pleasant and colorful. Aabal recognizes objects with old colors. The hue of rainbow colors made of seven colors attracts our mind a lot. Whether it is the redness of the sun, the blue of the space, the black color of the clouds or the series of mountains covered with snowy white sheets - the amazing beauty of all fascinates us. रंगों की अपनी भाषा है। रंग ही हमारा जीवन हैं। जीवन के विविध क्षेत्रों में ये रंग अपनी छटा बिखेरते हैं। खान-पान, रहन-सहन, पूजा-पाठ, धर्म-कर्म सभी तो विविध रंगों से जुडे हुए हैं।दुनिया के इस रंगमंच पर हर इंसान किसी-न-किसी रंग में रंगा हुआ है। रंगों की अनुभूति देखने व स्पर्ष करने से होती है।रंगों के बिना हमारा जीवन ठीक वैसा ही है, जैसे प्राण बिना शरीर । प्रकृति सौंदर्य में जहाँ ये रंग चार चाँद लगाते हैं वहीं मानव जीवन को भी सरस, सुखद व रंगीन बना देते हैं ।आबाल वृद्ध रंगों से वस्तुओं को पहचान लेता है। सात रंगों से निर्मित इन्द्रधनुष के रंगों की छटा हमारे मन को बहुत आकर्षित करती है। सूर्य की लालिमा हो, अंतरिक्ष की नीलाभा हो, मेघों का श्याम रंग हो या पर्वतों की श्रृंखला बर्फीली सफेद चादर ओढ़े हुए हो - सभी का अद्भुत सौंदर्य हमें मोहित कर लेता है।